Student Academic Performance: The Role of Antecedents, Mediation, and Moderation - Safira, Dea Salma; Ekowati, Dian (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study aims to investigate students' academic performance by examining the role of knowledge hiding (KHi) as a mediating variable and using three antecedents as dependent variables. Additionally, it explores the moderating role of academic self-efficacy on KHi behavior and students' academic performance. The research objectives should be expressed clearly and concisely. Design/Methods/Approach: Eleven hypotheses were analyzed using structural equation modeling (SEM). Data were collected through a primary survey based on structured questionnaires, with a sample size of 252 undergraduate students from various universities. Findings: Performance motivation and sense of relatedness positively affect academic performance, while territoriality of knowledge negatively affects academic performance. Territoriality of knowledge and sense of relatedness increase KHi. Meanwhile, performance motivation doesn't notably influence it. KHi partially mediates the impact of knowledge territoriality and fully mediates the effect of relatedness on academic performance. Academic self-efficacy doesn't significantly moderate the relationship between KHi and academic performance. Originality/Value: The study was conducted among students, bringing an academic perspective into the KHi literature. This study contributes new insights from a developing country to human resource management by examining KHi and academic performance within higher education—a previously unexplored context. Conducted among students, it enriches the KHi literature with valuable academic perspectives. Practical/Policy implication: This study presents exciting insights for administrators and policymakers in academia. By establishing a model, the research highlights that the phenomenon of KHi exists among students, which may or may not have immediately apparent negative effects, especially when compared to an organizational context. However, it certainly does not bode well for their future in the workforce, where indulging in knowledge hiding within teams or groups as employees can be detrimental.